ECEC teachers' emotional support during children's transition from home to ECEC - Golkhou, Mina (2024)
The present research investigates the role of early childhood education and care (from now on ECEC) teachers’ emotional support in smooth transitions for young children experiencing ECEC. Therefore, different strategies that ECEC teachers apply to support children emotionally and children’s reactions to those strategies are analyzed in detail to find new ways of reducing the anxiety and stress that children may feel at the time of separating their parents and entering their social environment. The participants of this research were 7 children (4 girls and 3 boys) aged 0 to 3 and 4 ECEC teachers from a Finnish kindergarten. Data was collected qualitatively through observations of children and interviews with ECEC teachers. Thematic analysis was applied for analyzing the collected data. According to the results, ECEC teachers apply different strategies for making transition smoother for young children. They can distract children from the transition situation or give them feeling of being safe by hugging, stroking or allowing children to bring their favorite toy or picture. Moreover, the proper decisions and behavior of ECEC teachers according to different situations can play a vital role for children’s smooth transitions. However, the results show that children may accept or reject the emotional support which they receive from ECEC teachers. The findings of this study can raise awareness of the real need of proper emotional support for young children during their transition from home to ECEC and can be a source of valuable information for daycare policy makers and caregivers.